The effect of neighbouring contacts on the formation of behavioral types in Black‐headed Gull chicks - M. A. Minina; A. V. Druzyaka (Юг России: экология, развитие)
Aim. The early development of behavioral types and the influence of environmental, mostly social, factors have almost not been studied for natural animal populations. We investigated the effect of the density of non‐relative social environment on the development of the behavior of free‐living chicks of the Black‐headed Gull (Chroicocephalus ridibundus). Material and Methods. In order to exclude the influence of relationships with native parents on the development of chicks' behavior, 21 clutches were cross‐fostered so as to destroy any negative relationship between the aggressiveness of their parents and the density of their neighbors. The behavioral types of chicks were determined by a 3‐time testing in an “open field” arena at the ages of 2‐3, 8‐9 and 14‐15 days.Results. Those parents, which effectively coped with close neighboring at the nest settling period, raised more active offspring. The behavior of chicks raised by foster parents, on the contrary, was more passive the fewer unrelated chicks there were nearby and was not associated with the aggressiveness of their parents.Conclusion. Our work demonstrates the role of an unrelated social environment in the ontogeny of behavioral types in colonial birds. We suppose that the different ways in which influences of parents and neighbors optimize the trajectories of development of behavioral types at an individual level, increase the chances of chicks surviving in the diverse and variable environment of a breeding colony.